Rolling stock emission testing methodology assessment for Balise Transmission Module system interoperability. (January 2016) - Adin, I.; Mendizabal, J.; Arrizabalaga, S.; Alvarado, U.; Solas, G.; Rodriguez, J.
Highlights: Rolling stock emissions procedure proposal. Completion of Subset 116. The Time–Frequency analysis narrows the transients' effects. Abstract: The interoperability between on track balises and the on board Balise Transmission Module systems depends on both sides' susceptibility and allowed emissions. For that assessment, the document that governs the testing methodology, tools and procedures (Subset 116) needs to be completed prior to its publication. The present paper proposes an advance beyond the state of the art for the rolling stock emission assessment in terms of the test setup and of the post-processing procedure. The documentation commonly used in ERTMS-related issues has been analyzed and the common tools and procedures have been taken into consideration for the proposal presented by the authors.